'Scarless reverse umbilicoplasty': A new technique of umbilical transposition in abdominoplasty. Issue 4 (April 2019) - Reho, A.; Randisi, F.; Ferrario, A.; Taibi, D.; Russo, F.; De Santo, L.; Stefanizzi, G.
Summary: Introduction: The navel plays a major role in the aesthetics of the abdomen. A navel that is abnormally shaped, malpositioned or has evident scarring may compromise the outcome of an otherwise well-executed full abdominoplasty. The aim of the technique in question is to recreate a navel that looks natural, with no visible scar, and that is properly positioned. Materials and methods: The technique was performed in 147 abdominoplasties of patients of both sexes (123 females and 24 males), with an average age of 35 years and a mean BMI of 24 kg/m 2 . The procedure involves the creation of a navel of reduced size, 10 × 5 mm, and its inset in the abdominal wall. Subsequently, the as-yet-not sutured abdominal flap is extended caudally to determine the point of projection of the navel. The abdominal skin is marked, the flap is reversed and an internal suture is carried out. Results: The appearance of the navel is aesthetically pleasant and natural looking and with no visible scarring. In addition, the position of the umbilicus is always correct. At the two-year follow-up, the results remain stable. No major complication occurred. Conclusions: The technique allows for the attainment of an extremely natural looking navel that satisfies the aesthetic criteria of attractiveness without visible scarring. The navel is always correctly positioned, without requiring measurements during surgery. The procedure is rapid, and although it does require a short learning curve, the results are extremely aesthetically pleasing and reproducible. The patient satisfaction rate is extremely high.